Social States : China in International Institutions, 1980-2000 - Johnston, Alastair I. (Book collections on Project MUSE., 2008)
'Social States' tests the effects of socialisation in international relations - to help explain why players on the world stage may be moved to cooperate when doing so is not in their material power interests. This book examines three microprocesses of socialisation.